2002
DOI: 10.1016/s0304-3959(02)00102-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of systemic morphine suggests a fundamental difference in the mechanisms that generate bone cancer vs. inflammatory pain

Abstract: Pain is the cancer related event that is most disruptive to the cancer patient's quality of life. Although bone cancer pain is one of the most severe and common of the chronic pains that accompany breast, prostate and lung cancers, relatively little is known about the mechanisms that generate and maintain this pain. Recently, we developed a mouse model of bone cancer pain and 16 days following tumor implantation into the intramedullary space of the femur, significant bone destruction and bone cancer pain-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 51 publications
7
125
0
4
Order By: Relevance
“…Morphine analgesia, also, does not affect limb use during forced ambulation, which is decreased (as expected) in the bone cancer pain model (66). Only very high doses (40 mg/kg) produced some slight amelioration, consistent with other observations, as well (37). This may help explain the fact that pain with activity or movement in humans, suffering from metastatic bone disease, may often be resistant to analgesic therapy with opioids or require high doses for suppression.…”
Section: Opioidssupporting
confidence: 87%
See 1 more Smart Citation
“…Morphine analgesia, also, does not affect limb use during forced ambulation, which is decreased (as expected) in the bone cancer pain model (66). Only very high doses (40 mg/kg) produced some slight amelioration, consistent with other observations, as well (37). This may help explain the fact that pain with activity or movement in humans, suffering from metastatic bone disease, may often be resistant to analgesic therapy with opioids or require high doses for suppression.…”
Section: Opioidssupporting
confidence: 87%
“…The correlation between anatomical progression and behavioral manifestations of pain, as well as similarities in the relative potency of treatments needed to suppress pain, indicate also the fact that this model simulates reliably several features of the clinical disease in humans. With regards to the latter, it has been shown that both the pain behavior induced in the mouse model of bone cancer pain, as well as the clinical pain in humans with bone metastases, are equally poorly responsive to opioids, compared to inflammatory pain (37). These observations validated the mouse metastatic bone pain model as adequate to elucidate mechanisms responsible for bone cancer pain, as well as the pertinent pharmacology, which may guide the development of new drugs to fight this type of pain (38).…”
Section: The Mouse Bone Cancer Pain Modelmentioning
confidence: 99%
“…This dose range of morphine is similar to that previously reported as being effective in blocking bone cancer pain-related behaviour in a mouse bone cancer pain model. 18,19 The effects of morphine were antagonized completely in response to naloxone, and the effects of the α-2 agonists were completely antagonized by idazoxan. These data support the concept that the action of morphine is mediated via activation of naloxone-sensitive opioid receptors, and that the effects of α-2 agonists are mediated via activation of idazoxan-sensitive α-2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has been reported that systemic administration of morphine produces an analgesic effect in this model, although the potency of morphine appears to be lower in the bone cancer pain model compared to the inflammatory pain model. 18,19 This suggests the existence of a different mechanism underlying bone cancer pain vs inflammatory pain. In the present study, the authors investigated the analgesic effects of ip administered α-2 receptor agonists dexmedetomidine and clonidine, NMDA receptor antagonists MK801 and ketamine, and the NAAG peptidase inhibitor ZJ-43, and compared the analgesic effect of these drugs with that of morphine in an animal model of bone cancer pain.…”
Section: Conclusion : Les Agonistes α-2 Produisent Un Effet Analgésiqmentioning
confidence: 99%
“…There are many models but in general they can be attributed to three main pain groups according to their etiology: inflammatory, cancer, and neuropathic pain. Several drugs such as opioids, [1][2][3] nonsteroidal anti-inflammatory drugs (NSAIDs), 4,5 IL-1 receptor antagonist, 6 or antibodies, e.g., anti-nerve growth factor (NGF) 7 and anti-tumor necrosis factor (TNF)-α, 8 were studied in cancer pain models showing different efficacy. In neuropathic pain also opioids, [9][10][11] purinergic receptor antagonist, 12 and enkephalindegrading inhibitors 13 have been tested.…”
Section: Pain and Inflammationmentioning
confidence: 99%